Fractured continent Europe's crises and the fate of the West - Drozdiak, William (New York W.W. Norton & Company, 2017)
Berlin : the new epicenter of power -- London : the breakaway realm -- Paris : in search of lost glory -- Brussels : capital of Europe, Tower of Babel? -- Madrid : will the center hold? -- Rome : the eternal city, forever in decline? -- Warsaw : between East and West -- Copenhagen : the green welfare state in peril? -- Riga : in the shadow of the bear -- Athens : l ife on the edge -- Moscow, Ankara, Tunis : Europes troubled neighborhood -- Washington, D.C. : the illusion of America first -- Epilogue : a post- American Europe?
Includes bibliographical references and index.
Keywords: Political stability--Europe.